Table of Content - - (Journal of Educational and Psychological Sciences, 2023)
Table of Content1. The reality of the practice of the principals of public schools in Jeddah Governorate for the interactive theory of leadership and its relationship to the level of administrative  creativity they have from their own point of view in light of the Corona pandemicMrs. Sharefa Ali Alzahrani , Prof. Najat Mohammad Alsaigh2. King Abdulaziz University students’ compliance with the values of digital citizenship in light of Islamic education directivesProf. Abdullah Attitallah Alahmadi3. The Effect of Send- A problem Strategy in Acquiring Methods of teaching Concepts and Developing Teamworking Competency of Higher Education StudentsDr. Sattar Jabbar Haji4. The Educational Implications Deduced from the Meccan Forty Hadiths and Their Applications  in the Meccan Society – A Field Study on the Workers in the Project of Venerating the Sacred Land –Mr. Faris Abdullah Alhebi5. The reality of the professional competencies of special education coordinators and teachers working with autism spectrum disorder in the Emirate of Abu Dhabi in the light of quality requirementsDr. Ashraf Mohamed Moustafa , Mrs. Marwa Maher Almelah6. Mindfulness and its relationship to creative self-efficacy among gifted students in the educational directorates of HebronDr. Sawsan Jamal Qabaga7. The Perception of English Language Teachers of the Importance of e-Learning Platforms in Hebron and Yatta GovernoratesMrs. Remah Ali Bhais, Dr. Ibrahim Moh’D Arman, Mr. Awni Moh’D Abu Tair
Keywords: Journal of Educational and Psychological Sciences